Modelling the Interaction between Carboxylic Acids and Zinc Oxide: Insight into Degradation of ZnO Pigments - Jihan Lubani; Filippo De Angelis; Daniele Meggiolaro; Laura Cartechini; Simona Fantacci (Molecules, 2022)
Computational modelling applied to cultural heritage can assist the characterization of painting materials and help to understand their intrinsic and external degradation processes. The degradation of the widely employed zinc oxide (ZnO)—a white pigment mostly used in oil paints—leads to the formation of metal soaps, complexes of Zn ions and long-chain fatty acids coming from the degradation of the oil binder. Being a serious problem affecting the appearance and the structural integrity of many oil paintings, it is relevant to characterize the structure of these complexes and to understand the reaction pathways associated with this degradation process. Density functional theory (DFT) calculations were performed to investigate the adsorption of the acetate and acetic acid on relatively large ZnO clusters and the formation of Zn–acetate complexes. Carboxylic acids with longer alkyl chains were then investigated as more realistic models of the fatty acids present in the oil medium. In addition, DFT calculations using a periodic ZnO slab were performed in order to compare the obtained results at different levels of theory. Optimization calculations as well as the formation energies of the ZnO@carboxylate coupled systems and the thermodynamics leading to possible degradation products were computed. Our results highlight the potential for DFT calculations to provide a better understanding of oil paint degradation, with the aim of contributing to the development of strengthening and conservation strategies of paintings.